In the heat of the night [videorecording (DVD)] - Poitier, Sidney; Steiger, Rod, 1925-2002; Oates, Warren, 1928-1982 (MGM Home Entertainment, 2008)
Virgil Tibbs is a renowned homicide detective from Philadelphia returning to Mississippi in the sweltering summer to visit his mother, when a rich factory owner is found dead. The industrialist was white, Tibbs is black and in the Deep South at the time, that is enough reason for the local cops to arrest him on suspicion murder. After his identity and credentials are established, the Chief of Police lets Tibbs go and attempts to enlist his help in solving the case. An uneasy and complicated relationship develops between the southern Sheriff and the city slicker. Sidney Poitier stars as the superior sleuth who rediscovers the small town racism he escaped through his education. Rod Steiger is the local sheriff who is forced to examine his own prejudices and repent them.